Evaluation of aerial spraying application of multi-rotor unmanned aerial vehicle for Areca catechu protection - Wang, Juan; Ma, Chao; Chen, Pengchao; Yao, Weixiang; Yan, Yingbin; Zeng, Tiwei; Chen, Shengde; Lan, Yubin (Frontiers in Plant Science, 2023)
Unmanned aerial vehicles (UAV) sprayers are rapidly becoming a new application tool in East Asia, especially in China. The current application of UAV spraying focuses on field crops, and the potential advantages of tall and dense crops in hills are worthy of further exploration. The tropical crop areca catechu has upright, tall stalks, up to 30 m. There is still a lack of suitable, low-risk automated spraying devices for areca catechu. We studied the application of an electric multi-rotor UAV for plant protection of areca catechu and compared the droplet deposition distribution of the UAV at two operating speeds and three flight altitudes in two leaf area indices (LAI) of areca catechu by setting copper plate cards for droplet deposition sampling in the crop canopy, ground, and drift areas. The results showed that the larger the LAI of areca catechu, the denser the branches and leaves, and the less droplet coverage, the maximum coverage was 4.28%, and the lowest was 0.33%. At v=1.5 m/s showed a tremendous ground loss, while the canopy droplet deposition also got the best penetration. The overall deposition effect was poor at flight altitudes greater than 11.09 m and velocities greater than 2.5 m/s. Comparing v=2.5 m/s to v=1.5 m/s, the overall distance of 90% of the total drift increased to double under the same operating parameters. This study presents promising data to support the innovative integration of UAVs into crop protection programs for tall trees such as areca catechu. It may guide future research to develop relevant labeling recommendations.